Snow occurrence time on the Russia’s territory in the early 21st century (from satellite data) - T. B. Titkova (Lëd i Sneg, 2017)
Time of the snow cover appearance, existence and disappearance on the Russia’s territory in the early 21st century (2000–2015) was corrected using the MODIS/Terra satellite data (the 8-day discreteness, and the 0.5×0.5° resolution). The satellite data errors were estimated from data of the ground stations observations. The errors were found to be maximal in autumn and minimal in spring. The relationship between the snow cover characteristics and the climate ones was investigated using data obtained at the ground-based stations together with correlation between dates of snow appearance and loss and the climate parameters. The dependences obtained were tested by means of correlation and regression analysis over the longitudinal sectors. Significant coefficients of correlation (the Student criterion of probability was equal to 0.95) were found between time of the snow cover presence and dates of the temperature drop below 0 °С and the amount of days with negative temperatures. Changes in the climate characteristics result in that due to decreasing of the solid precipitation in winter time the snow presence duration becomes shorter over the European part of Russia and in the Western Siberia. The shortening in the Middle Siberia is caused by the spring warming. Durations of the snow occurrence in the Far East area are different. On the Chukotka peninsula the duration is longer because of the autumn fall in temperature while in the Kamchatka region the snow occurrence time is shorter due to significant decrease of a period with negative temperatures in both the autumn and spring seasons.